2010
DOI: 10.1111/j.1600-0706.2009.17840.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, intensity‐dependence, and host manipulation in the trematodeCurtuteria australis: following the strategies of others?

Abstract: Manipulation of host phenotype by parasites can require a collective effort from many individuals. The cost of manipulation may only be paid by the individuals actually inducing the manipulation, while its benefits are reaped by all. Here, we determine if there is genetic variation in manipulative effort among different clonal lineages of the trematode Curtuteria australis, and whether the decision to manipulate is context‐dependent. C. australis impairs the burrowing efficiency of its second intermediate host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…Yan et al, 1994;Franceschi et al, 2010) (see also Leung et al, 2010). Indeed, strain formation itself is a bugaboo for experimenters who maintain animals in the laboratory.…”
Section: Genetics and Variationmentioning
confidence: 99%
“…Yan et al, 1994;Franceschi et al, 2010) (see also Leung et al, 2010). Indeed, strain formation itself is a bugaboo for experimenters who maintain animals in the laboratory.…”
Section: Genetics and Variationmentioning
confidence: 99%
“…, 2001; Kaltz & Shykoff J, 2002), but very little is known about behavioural manipulation. Only the results of Leung et al. (2010) suggest that there could be variation between trematode clones from the same natural population in their ability to reach the host tissues where they can express host manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Gosner 20, p ¼ 0.035). Anaesthetized tadpoles had significantly more metacercarial infections in the head than tail, whereas non-anaesthetized tadpoles had predominately tail infections; anaesthesia did not affect encystment in the mid-body region (figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Leung et al [20] revealed a positive relationship between metacercarial intensity and trematode recruitment to a particular host body location in the cockle Austrovenus stutchburyi. If the same pattern occurred for the focal trematode and host in this study, then it could have implications for the effect of cercarial encystment location on host mass gain.…”
Section: Methodsmentioning
confidence: 99%